MODEL CBT-DE (Computer Bassed Test For Digital Entrepreneurship) Yang Adaptif Dan Terintegrasi Menggunakan Mobile-Virtual Learning Untuk Pendidikan Kewirausahaan Diperguruan Tinggi - ., Sularno; ., Zulfahmi; Anggraini, Putri; Amanda, Wilia Zulkifni (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2024)
This research aims to develop an entrepreneurial learning model in higher education using the CBT-DE (Computer Bassed Test For Digital Entrepreneurship) model which is adaptive and integrated using mobile-virtual learning. Problems that often occur with CBT that have been developed include 1) low level and nature of test adaptation, 2) flexible size and unit of test administration, 3) user interface issues, 4) automated test assembly and test quality control, 5 ) security risks. Overcoming the problems above requires smart solutions, which are able to overcome current and future problems. One of the solutions offered to overcome this problem is to modify the old test model with a computer-based test model CBT-DE (Computer Bassed Test For Digital Entrepreneurship) using adaptive and integrated Mobile-Virtual Learning using an expert system. The use of an expert system in the CBT-DE model aims to make it easier to modify the system, can be used on various types of computers and other mobile devices which will be useful in integrating systems, has the ability to adapt, and has reliable information facilities. With this research, the CBT-DE (Computer Bassed Test For Digital Entrepreneurship) model uses Adaptive and Integrated Mobile-Virtual Learning which is able to provide material sharing and entrepreneurship education assessment tests to students in identifying students who have entrepreneurial talent and those who do not have entrepreneurial talent. . So that in the future the vision and mission of Dharma Andalas University can be achieved as a University based on Technopreneurship (technology and entrepreneurship). The research method used in developing this model is the research and development (R and D) method with the 4 D model. The expected output of this research will be a model, a product in the form of a CBT-DE application, publication in a Scopus indexed international journal, and proceedings Scopus indexed international seminar.